THE EFFECT OF SEX (GENDER) ON THE SUCCESS OF BUSINESSWOMEN IN THE BUSINESS ENVIRONMENT IN MARKETING IN JORDAN (AN EMPIRICAL STUDY) - Falah Al-zoubi, Ali (British Journal of Marketing Studies, 2014)
The aim of this study is to address gender barriers in the business environment in Jordan. Two variables that may influence economic success of businesses owned by women entrepreneurs in Jordan were selected for this purpose. These variables are the marital status of female entrepreneur and its effect on her business, while the second variable is related to gender discrimination and whether it is considered a major obstacle facing women entrepreneurs. To analyze data collected from 102 convenient sample of female business owners in private sector and different innovation centers the linear model was used to identify the relationship between the marital status and gender discrimination and success in business. The result of this study shows a positive relationship between the marital status of business owners and success in business and that being a female or single is not an obstacle facing Jordanian women in business. The implications of the results are briefly highlighted.